2011
DOI: 10.1098/rspb.2011.0881
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic differences of mammalian basal metabolic rate are not explained by mitochondrial basal proton leak

Abstract: Metabolic rates of mammals presumably increased during the evolution of endothermy, but molecular and cellular mechanisms underlying basal metabolic rate (BMR) are still not understood. It has been established that mitochondrial basal proton leak contributes significantly to BMR. Comparative studies among a diversity of eutherian mammals showed that BMR correlates with body mass and proton leak. Here, we studied BMR and mitochondrial basal proton leak in liver of various marsupial species. Surprisingly, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…This is due to a decrease in the mitochondrial proton conductance in the heaviest individuals. Interestingly, the negative relationship found between mitochondrial proton leak and M b in frogs is similar to that in endothermic groups such as mammals (Porter and Brand, 1993), including marsupials (Polymeropoulos et al, 2012), and birds . Finally, and in contrast to our prediction, we found that liver mitochondria from the larger individuals produced significantly lower levels of ROS than those from the smaller animals.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…This is due to a decrease in the mitochondrial proton conductance in the heaviest individuals. Interestingly, the negative relationship found between mitochondrial proton leak and M b in frogs is similar to that in endothermic groups such as mammals (Porter and Brand, 1993), including marsupials (Polymeropoulos et al, 2012), and birds . Finally, and in contrast to our prediction, we found that liver mitochondria from the larger individuals produced significantly lower levels of ROS than those from the smaller animals.…”
Section: Discussionmentioning
confidence: 51%
“…However, such interspecific correlation between mammalian M b and mitochondrial ROS generation is not systematically found, being mostly revealed when isolated mitochondria oxidize succinate in the absence of rotenone (Lambert et al, 2007) or when cells are metabolically stressed (Csiszar et al, 2012). However, it is apparent that the negative relationship reported between M b and proton leak (Porter and Brand, 1993;Porter et al, 1996;Polymeropoulos et al, 2012) cannot be associated with a positive allometric variation in ROS generation (Sohal et al, 1989(Sohal et al, , 1990Ku et al, 1993;Lambert et al, 2007;Csiszar et al, 2012). A similar result has been found in birds, with M b shown to be negatively correlated with both proton leak and ROS generation in liver mitochondria respiring on succinate (Lambert et al, 2007;Montgomery et al, 2012).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Recent investigators have implicated membrane composition and function [89,167,179,234], mitochondrial activity and number [97,179,[235][236][237], intracellular transport costs [130], DNA content [182,190], and other biochemical factors [238], as importantly involved in the intrinsic cellular control of metabolic scaling. Evidence for and against various specific aspects of this approach can be found in [19,20,89,[91][92][93][94]130,167,169,[235][236][237][238][239][240][241][242][243]. A major limitation of the cell-based RD approach is that it cannot explain by itself why the hypometric scaling of cellular metabolic rate is lost in cells cultured in vivo (reviewed in [20,97]).…”
Section: Resource-demand Modelsmentioning
confidence: 99%